SERUM CHROMIUM, MAGNESIUM AND ZINC LEVELS IN SUDANESE TYPE 2 DIABETIC PATIENTS - Elsonni Abdalla, Badreldin; A. Diab, Abdelgader; Yousif Zaki, Hani; Eltom Ali, Khalid (Gezira Journal of Health Sciences, 2011)
Objectives: The purpose of this study was to evaluate the difference in serum chromium, magnesium and zinc levels between diabetic and control groups, and to determine the correlations between these elements and serum glucose in patients with type 2 diabetes mellitus. Methods: Forty patients suffering from type 2 diabetes and 30 controls were selected randomly. The level of serum chromium, magnesium and zinc were measured and compared between the two groups. Correlations of serum Cr, Mg and Zn with serum glucose were conducted. Results: There was a very significant difference in some serum trace elements level between diabetic and control groups. Serum magnesium and zinc were significantly lower in diabetic group compared with the control group (P= 0.014, P < 0.0001 respectively). Negative but not significant correlations were shown between Cr, Mg and Zn and serum glucose. ConclusioN: There is trace elements metabolism disorder in patients with type 2 diabetes mellitus. Magnesium and zinc could be considered suitable for inclusion in a nutritional supplement for diabetes with significant value for the treatment of diabetics and prevention of complications.